ACOUSTIC EMISSIONS ANALYSIS AND 2-D P-WAVE TOMOGRAPHY ALONG A ROUGH LABORATORY FAULT UNDERGOING STICK-SLIP CYCLES - JIN, ZIROU (My University, 2018)
The distributions and magnitudes of seismicity within fault systems could be highly influenced by the heterogeneity of shear stress field according to the geometric structure, fractures and asperities. However, the statistics of earthquakes has been well demonstrated to follow a robust frequency-magnitude relation (i.e., Gutenberg-Richter relationship) and the slope of which (i.e., b-value) was noticed to decrease within or near the rupture region before large earthquakes (M ≥ 5). To investigate the underlying physical mechanism, we conducted triaxial deformation experiments with stick-slip sequences along rough faults, during which we recorded the acoustic emissions (AEs) accompanying with the crack formation in rock and measured p-wave velocity periodically for 2-D tomography along the fault. The present work analyzes the potential connections between the fault topography, which is revealed by X-ray computer tomography (CT) images and white-light profilers, and the spatial distribution of AE hypocenters, moment release and b-value along the fault. We found that the slip events tended to nucleate within or in the proximity of a region that had consistently limited foreshock activities (i.e., an “AE gap” region) during the stick-slip cycles and the “AE gap” region also showed a spatial correlation with the structural asperity on the fault surface. As for the b-value analysis, we computed an average b-value of 1.14 based on all AEs occurred in the experiments and observed a spatial anti-correlation between the AE clusters and the anomalously low b-value region. In addition, all ten slip events were found to initiate within or near regions with high moment release, and seven of them were observed to correlate with low b-value patches. In terms of the velocity structure, we observed a horizontal boundary at the middle of the fault plane (higher p-wave velocity in the bottom half of the fault plane) and a “velocity-increase” region that underwent velocity increase upon slips. However, a higher-resolution velocity structure is required to reveal more velocity heterogeneities on fault and in turn gain further insights into the analysis of the b-value - stress relation.